Impact of Irrigation, Crude Oil Prices, and Agricultural Loans to the Philippines’ Agricultural Output - Joseph Su Bi G. Dela Cruz Cruz; Geranina Joy A. Lim Lim; Josefino JR C. Ocampo Ocampo; Marie Antoinette L. Rosete Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2022)
This study examines the impact of Irrigation, Crude Oil Prices, and Agricultural Loans to the Agricultural Output. The data used are secondary which were compiled from different The Independent Variables used are Irrigation, Crude Oil Prices, and Agricultural Loans while the Dependent Variable used is the Agricultural Output. The coverage of this study is from 1991 - 2020. This is a quantitative approach to empirically determine the relationship between the independent variables to the dependent variable. The main tests that the researchers used are Ordinary Least Squares regression (OLS), Multicollinearity test, and through the use of a Q-Q plot to determine any outliers in the data. The researchers were successful in determining the relationships among the variables. It has been determined that Irrigation and Crude Oil Prices have a positive relationship towards the Agricultural Output while there is a negative relationship between Agricultural Loans and the Agricultural Output.